Ovarian Cancer Cells Promote Glycolysis Metabolism and TLR8-Mediated Metabolic Control of Human CD4+ T Cells - Shang, Wenwen; Xu, Rui; Xu, Ting; Wu, Ming; Xu, Juan; Wang, Fang (Frontiers in Oncology, 2020)
An immunosuppressive microenvironment is a major obstacle for successful tumor immunotherapy. Elucidating the regulatory mechanisms of energy metabolism and functionality in CD4+ T cells will provide insights for the development of novel immunotherapies for ovarian cancer (OC). An Agilent microarray was used to detect differences in gene expression between peripheral CD4+ T cells from five OC patients and those from five healthy controls. Functional pathway analysis was performed for differentially expressed genes. Gene expression profiles revealed significant differences in expression levels of 5,175 genes in peripheral CD4+ T cells from five patients with OC. Functional analysis indicated that the most significantly enriched pathways were metabolic pathways. Furthermore, eight glycolysis-related genes all showed significantly increased expression in peripheral CD4+ T cells of OC patients. Moreover, we established a coculture system of human CD4+ T cells with the OC cell line SKOV3, and then treated them with toll-like receptor 8 (TLR8) ligand ssRNA 40. Coculturing with SKOV3 cells could increase the expression of the eight glycolysis-related genes, promote glucose uptake and glycolysis in CD4+ T cells, induce the differentiation of CD4+ CD25+ Foxp3+ T cells, and enhance the suppression of naïve CD4+ T cells. Additionally, activated TLR8 signaling could mediate the reprogramming of glycolysis metabolism and function in CD4+ T cells. Overall, our study indicates that the SKOV3 coculture environment could regulate the glycolysis metabolism and function of CD4+ T cells, and also that TLR8 mediated the metabolic control of glycolysis in CD4+ T cells cocultured with SKOV3 cells. This provides a new direction for immunotherapy investigations in OC.